2019
DOI: 10.3390/molecules24061060
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Heterocyclic-Based 4H-benzo[h]chromene Moieties: Targeting Antitumor Caspase 3/7 Activities and Cell Cycle Analysis

Abstract: Novel fused chromenes (4,7–11) and pyrimidines (12–16) were designed, synthesized, and evaluated for their mammary gland breast cancer (MCF-7), human colon cancer (HCT-116), and liver cancer (HepG-2) activities. The structural identity of the synthesized compounds was established according to their spectroscopic analysis, such as FT-IR, NMR, and mass spectroscopy. The preliminary results of the bioassay disclosed that some of the target compounds were proven to have a significant antiproliferative effect again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In addition, 4H-benzo[h]chromene derivatives are a very successful choice in the treatment of several human diseases. For instance, some derivatives of 2-amino-4-aryl-4H-benzo[h]chromene-3-carbonitrile and 2-amino-4-aryl-6-methoxy-4H-benzo[h]chromene-3-carbonitrile act as potential tumor vascular-disrupting agents and induce cell cycle arrest at G2/M and apoptosis [11,12], thus they have emerged as a new class of cytotoxic agents [13][14][15][16][17][18][19][20][21]. In addition, a range of studies has revealed the potential anticancer effect of 1H-benzo[f]chromene derivatives [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 4H-benzo[h]chromene derivatives are a very successful choice in the treatment of several human diseases. For instance, some derivatives of 2-amino-4-aryl-4H-benzo[h]chromene-3-carbonitrile and 2-amino-4-aryl-6-methoxy-4H-benzo[h]chromene-3-carbonitrile act as potential tumor vascular-disrupting agents and induce cell cycle arrest at G2/M and apoptosis [11,12], thus they have emerged as a new class of cytotoxic agents [13][14][15][16][17][18][19][20][21]. In addition, a range of studies has revealed the potential anticancer effect of 1H-benzo[f]chromene derivatives [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A series of novel heterocyclic incorporated 4H-benzo[h] chromenes were designed and synthesized and evaluated for their anticancer specific potency against targeted cancer cell lines (Alblewi et al, 2019a ). As a result, compounds 59 and 60 showed higher anticancer activity toward the all targeted cancer cell lines with IC 50 ranges of 0.7 to 3.0 μg/mL and 0.8 to 1.4 μg/mL, respectively.…”
Section: Biological Activities Of 2h/4h-chromenesmentioning
confidence: 99%
“…Therefore, compounds 59 and 60 trigger cell apoptosis by the activation of caspse3/7 and executioner DNA fragmentation in cancer cells. Additionally, these compounds also exhibited a substantial reduction in cell invasion and cell migration parentage (Alblewi et al, 2019a ). These compounds are potent lead molecules for the development of anticancer drug molecules.…”
Section: Biological Activities Of 2h/4h-chromenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mccarroll and co-workers also reported that tephrosin, a viable anti-lung carcinoma drug, as well as Acronycine, a drug targeting colon, lung, and ovary tumors, obstruct the cell proliferation through their binding to the β-tubulin specific site, which subsequently induces apoptosis through microtubule polymerization [ 11 ]. Furthermore, chromene molecules are deemed ‘privileged medicinal scaffolds’ due to their unique pharmacological and biological activities [ 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%